Rate Of Interest, Payment Period, Collectability And Their Impact On Non Performing Loan - I Made Suasmarajaya; Ida Bagus Teddy Prianthara (Jurnal Manajemen dan Bisnis, 2015)
This study aims to determine: 1) the influence of interest rate on non-performingloan, 2) the influence of payment period on non-performing loan, 3)the influence ofcollectability on non-performing loan,, 4) the influence of interest rate on collectability, 5)the influence of payment period on collectability, 6) indirect effects of interest rate on nonperformingloan through collectability, 7) indirect effects of payment periodon nonperformingloan through collectability,8)simultaneous effects of interest rate, paymentperiod, collectability on non-performing loan. This research was conductedat PTPegadaian Branch Denpasar using 76 respondents who are employees and officials underinvestigation related to the type of credit. Sources of data used are primary and secondarydata. Variabels used are interest rate and payment period as independent variable,collectability as intervening variable, and dependent variable is non-performing loan.Data collection technique using questionnaires,while the data analysis method use dareresearch instruments includevalidity-reliability test, assesment of normality, outliers test,multicolinearity-singularity test and goodness of fit index; Hypothesis testing methodinclude path analysis, multiple square correlation (R2) as well as direct and indirect effectamong variable. The results showed that: 1) rate of interest has positive and significantinfluence on non-performing loan, 2) payment period has positive and significantinfluence on non- performing loan, 3) collectability significantly negative on effecttowards non-performing loan, 4) rate of interest significantly negative on effect towardscollectability, 5) payment period significantly negative on effect towards collectability, 6)there are indirect effects of interest rate on non-performing loan through collectability 7)there are indirect effects of payment period on non-performing loan through collectability,8) All variables have significant simultaneous effects on non-performingloan.Keywords : rate of interest, payment period, collectability, non performing loan